When God went to hell - Gupta, Ravi (New Delhi Niyogi Books, 2016)
When one dies, one wants to go to Heaven. Right?Wrong!!!That is what St Peter tells the assembly of gods as he explains the falling market share of human souls desirous of entering the portals of Heaven. It is the beginning of soul searching in Heaven, culminating in the decision to appoint a consultancy firm on earth to understand the radically changed human mind and make strategic course correction. Among the recommendations of the consultants, is the appointment of a CEO in Heaven.
Keywords: English Fiction; IPS as an author